Characterization measurements of the TRISTAN multi-pixel silicon drift detector. (1st September 2022) - Urban, K.; Carminati, M.; Descher, M.; Edzards, F.; Fink, D.; Fiorini, C.; Gugiatti, M.; Hinz, D.; Houdy, T.; King, P.; Lechner, P.; Mertens, S.; et al.
Abstract: Sterile neutrinos are a minimal extension of the standard model of particle physics. A laboratory-based approach to search for this particle is via tritium β-decay, where a sterile neutrino would cause a kink-like spectral distortion. The Karlsruhe Tritium Neutrino (KATRIN) experiment extended by a multi-pixel Silicon Drift Detector system has the potential to reach an unprecedented sensitivity to the keV-scale sterile neutrino in a lab-based experiment. The new detector system combines good spectroscopic performance with a high rate capability. In this work, we report about the characterization of charge-sharing between pixels and the commissioning of a 47-pixel prototype detector in a MAC-E filter.